2015
DOI: 10.1007/s13644-014-0184-z
|View full text |Cite
|
Sign up to set email alerts
|

My Friend is Gay, But… The Effects of Social Contact on Christian Evangelicals’ Beliefs about Gays and Lesbians

Abstract: This paper examines the relationship between social contact with gays and lesbians and beliefs about homosexuality, and explicitly investigates whether this relationship is different for Christian evangelicals than for others. We find that although social contact with gays and lesbians is related to beliefs about homosexuality in ways predicted by social contact theory, those with a gay or lesbian friend hold more positive attitudes, this is not the case for Christian evangelicals. In fact, analyses reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The negative associations between, from one side, older age, gender (i.e., being a man), lower education level, religiosity, and no contact with sexual minorities' members with, on the other side, endorsement of same-sex couples' and families' rights, replicate findings from previous studies conducted in Italy (Baiocco et al, 2013;Lingiardi et al, 2016;Petruccelli et al, 2015;Piumatti, 2017) and elsewhere (Brown & Henriquez, 2008;Davies, 2004;Hodson et al, 2009;Whitley Jr., 2009). Results from the moderating effect of contact are in accordance with a study by Baker and Brauner-Otto (2015) conducted on a large sample of adults from Texas (United States). They found that only among the most conservative religious individuals did the positive effect of social contact with gay men and lesbian women disappear.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The negative associations between, from one side, older age, gender (i.e., being a man), lower education level, religiosity, and no contact with sexual minorities' members with, on the other side, endorsement of same-sex couples' and families' rights, replicate findings from previous studies conducted in Italy (Baiocco et al, 2013;Lingiardi et al, 2016;Petruccelli et al, 2015;Piumatti, 2017) and elsewhere (Brown & Henriquez, 2008;Davies, 2004;Hodson et al, 2009;Whitley Jr., 2009). Results from the moderating effect of contact are in accordance with a study by Baker and Brauner-Otto (2015) conducted on a large sample of adults from Texas (United States). They found that only among the most conservative religious individuals did the positive effect of social contact with gay men and lesbian women disappear.…”
Section: Discussionsupporting
confidence: 87%
“…Among the strengths of the current research, we may certainly mention the use of a national representative sample. On the one hand, this confers strong representativeness to our results, as recommended to overcome the crisis of results' replicability in social psychology (Świaôtkowski & Dompnier, 2017), on the other hand, it contributes to extending previous findings on mainly Protestant samples from the United States (Baker & Brauner-Otto, 2015;Cunningham & Melton, 2013) to a large population from a Catholic country such as Italy. Indeed, Italy represents a particular context, being a country with high levels of Catholic religiosity, both as beliefs and concrete commitment, even in comparison to other Mediterranean countries, including Spain, France, and Portugal (Barcaccia et al, 2018;Bréchon, 2007;ILGA-Europe, 2019).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 72%
See 1 more Smart Citation
“…It is very plausible that widespread stigma against queers, perpetrated in part by the Christian community, is partially responsible for an underrepresentation of queer intellectual interests, including within philosophy. There is, furthermore, empirical research to suggest that gay students in Christian colleges face risks with their identities, 31 that Evangelical Christians are unusually unaffected by social contact with queers, 32 that conservative Christian calls for celibacy 33 or 'conversion therapy' 34 have an adverse effect on queer mental health despite the quasi-advocacy of the approach among some Evangelicals, 35 and that structural stigma against queers is a social determinant of health 36 and a predictor of under-involvement in college contexts that limit student success 37 . All of these negatively impact the extent to which queers are academically engaged and academically open about questions that interest them.…”
Section: Making Space For Queersmentioning
confidence: 99%
“…There is evidence that education about homonegativity can change a person’s attitudes about homosexuality (Baker & Brauner-Otto, 2014 ; Collier, 2012 ). A study performed on 125 men and women at a Catholic Liberal Arts University randomly recruited students by posting notices of the study in the Psychology Department.…”
Section: Introductionmentioning
confidence: 99%